ANALISIS PEMASARAN BAWANG MERAH DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Arman,Afandi, Silvana (AGROTEKBIS, 2016)
This research was conducted in Oloboju Village, Sigi Biromaru Sub District of Sigi District. Thirty three farmer respondents were selected from 50 farmers using simple random sampling method while two traders and two retailer respondents were chosen using tracing sampling method.Â Thus, the number of respondents was 37 respondents. The results of the analysis showed that the total marketing margin of the shallot obtained from first marketing channel was IDR 25,000 whereas from second marketing channel was IDR 26,000.Â The portions of price the farmers obtained were 96.2% and 86.7% from the first and second channels, respectively.Â The marketing channels of shallot in Oloboju village were (1) farmers â traders â retailers â consumers, and (2) farmers â retailers â consumers.Â The second marketing channel is more efficient